Urgensi Talak Di Depan Sidang Pengadilan Perspektif Maslahah Mursalah - Musda Asmara; Reti Andira (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
This paper aims to find the urgency of the divorce that must be imposed in front of the court as stipulated in article 115 Compilation of Islamic Law based on the review of maslahah mursalah. This was done because there was a controversy about the talak provisions in classical fiqh with the provisions of the divorce contained in the Marriage Law in Indonesia. The data presented in this paper are sourced from the literature. The results of this paper indicate that the review of Maslahah Mursalah against the imposition of divorce which must be done in front of the court is that the divorce has legal certainty for both husband and wife if they are to remarry, in addition to guaranteeing the child's livelihood and living for his wife, and the wife can claim the right to share property without this. In addition, the Religious Court is one of the institutions that can narrow divorce and at the same time can abort talak habits that are arbitrary.